PHILOSOPHICAL REFLECTIONS ON THE EVOLUTION AND SYMBOLIC INFLUENCE OF LANDSCAPE ELEMENTS IN METICULOUS AND COLOURFUL PAINTINGS OF THE MING AND QING DYNASTIES - Zhang, Yuxian (European journal for philosophy of religion, 2024)
Traditional Chinese landscape painting serves as a profound cultural and spiritual expression, reflecting the Chinese people's reverence for nature through symbolic representation, aesthetic philosophy, and artistic craftsmanship. Since its emergence during the Tang Dynasty, landscape painting evolved into a distinct art form characterized by spiritual contemplation and cultural symbolism. Its development through the Song, Yuan, Ming, and Qing dynasties led to the establishment of northern and southern schools, each with its unique techniques and philosophical underpinnings. In modern society, technological advancements and the influence of Western art have posed new challenges and opportunities for landscape painting. This study explores the philosophical and spiritual dimensions of landscape elements in traditional Chinese art while examining innovative techniques that merge classical aesthetics with modern artistic expressions. Through analyzing the works of key landscape painters, the study highlights advancements in thematic representation, stylistic innovation, and symbolic meaning, offering insights into how traditional landscape painting can be revitalized in contemporary art while preserving its cultural and spiritual heritage.